A Qualitative Exploration of the effect of Neuro-Linguistic Programming (NLP)-based coaching on emotional intelligence (EI) and leadership development among African Managers - Atimoe, Tim Itua; Iornem, Kohol; Akogwu, Praise R.; Senkoya, Michael A. (Technium Social Sciences Journal, 2026)
Background: Leadership effectiveness and emotional intelligence (EI) have become essential for organizational success, particularly among African executives navigating complex socio-cultural and global business environments. Neuro-Linguistic Programming (NLP)-based coaching, has been proposed as a transformative approach to developing these competencies. However, empirical research on its impact within the African context remains limited. This study therefore explores how NLP-based coaching influences EI and leadership development among African managers. Methods: A qualitative design was adopted involving in-depth semi-structured interviews with 21 African executives purposively selected from a prior survey of 394 respondents. Participants represented diverse sectors, including public, private, academic, and not-for-profit organizations. Data were analyzed thematically using NVivo software to identify psychological processes and behavioral outcomes emerging from NLP-based coaching. Ethical approval and informed consent were obtained, with confidentiality assured throughout. Results: Participants reported that NLP techniques such as reframing, anchoring, and meta-model questioning facilitated self-reflection, emotional control, adaptive communication, and increased leadership authenticity. These psychological shifts translated into improved decision-making, greater empathy, and stronger team engagement across organizational contexts. Conclusion: NLP-based coaching demonstrated significant potential in fostering emotional intelligence and transformational leadership behaviors among African executives.